Case Report: α1-antitrypsin deficiency causing persistent pleural effusion and multilobar alveolar emphysema in a young dog - Doulidis, Pavlos G.; Frizzo-Ramos, Carolina; Bertram, Christof A.; Grünzweil, Olivia M.; Kneissl, Sibylle M.; Degasperi, Brigitte; Hirt, Reinhard A.; Burgener, Iwan A.; Luckschander-Zeller, Nicole (Frontiers in Veterinary Science, 2025)
Alpha-1 antitrypsin deficiency (A1ATD) is a rare genetic condition in both humans and animals, caused by mutations in the SERPINA1 gene that lead to reduced or absent production of alpha-1 antitrypsin (A1AT). This case report describes a 3-year-old male dog presenting with persistent pleural effusion, chronic nonproductive cough, and respiratory distress. Despite an extensive diagnostic evaluation that included computed tomography (CT), a definitive diagnosis of A1ATD was only reached after a histopathological examination of lung tissue, which revealed acinar emphysema characterized by the destruction of alveolar walls. Serum A1AT levels were undetectable, confirming the diagnosis. The absence of liver involvement aligned with the lung-predominant phenotype described in human A1ATD. This is the first reported case of A1ATD-associated emphysema and pleural effusion in a dog, emphasizing the need for further research into its pathophysiology, diagnosis, and management in canine patients.